2023
DOI: 10.3389/fragi.2023.1279479
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity has a stronger correlation with arterial stiffness than strength, balance, or BMI in an older population

Hannah Hill,
Catherine A. Elliot,
Catherine A. Lizamore
et al.

Abstract: Background: Arterial stiffness is associated with an array of debilitating health conditions. While exercise typically has beneficial effects on both arterial stiffness and overall health, more research is needed to understand the associations of different types of fitness indices with arterial stiffness.Aim: To investigate the relationship between balance, strength, cardiovascular fitness and physical activity with arterial stiffness (as measured by pulse wave velocity (PWV)) in older adults.Method: Eighty re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“… 17 In addition, a stronger correlation between physical activity and arterial stiffness than other risk factors has been observed in older people. 18 Therefore, the effect of old age should be taken into account. Studies have shown that age also affects the amount of fat in the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“… 17 In addition, a stronger correlation between physical activity and arterial stiffness than other risk factors has been observed in older people. 18 Therefore, the effect of old age should be taken into account. Studies have shown that age also affects the amount of fat in the pancreas.…”
Section: Discussionmentioning
confidence: 99%